Unstoppable: A critical reflection on the socio-economic embeddedness of technology and the implications for the human agenda - Cloete, Anita Louisa (HTS teologiese studies, 2019)
The overall aim of the article is to unpack some of the layers of motivation that inform and shape the relationship between technology and education. This aim is motivated by the need for a more nuanced perspective on the complex relationship between technology and education. The discussion of technology and education would be utilised as springboard to provide a platform for elaborating on the complex nature of technology as medium, its broader impact on society and the kind of life it creates. The article names a few of the external and internal imperatives for the integration of technology into education. The first part of the title refers to the name of a film about an unmanned, runaway train with serious consequences for the environment and humanity at large. The idea is to relate the pervasive, self-enforcing nature and role of technology with the theme of the film, a force that seems to be unstoppable. It is argued that the integration of technology into education cannot be reflected in isolation from an understanding of the complex nature of technology and the broader functioning of technology in other spheres of life. The socio-economic embeddedness of technology is unpacked by discussing the mediatisation theory, technological development as a revolution and the Fourth Industrial Revolution. The final section describes the need for and possible processes to sharpen the focus on ethics in digital age.